2021
DOI: 10.1017/s1474746421000683
|View full text |Cite
|
Sign up to set email alerts
|

Extra Care Housing: The Current State of Research and Prospects for the Future

Abstract: Extra care housing aims to meet the housing, care and support needs of older people, while maintaining their independence in self-contained accommodation. Evidence from several studies suggests that it has benefits for residents in terms of costs and outcomes, and can provide a supportive environment for people with dementia, although the benefits for residents with greater care needs are less clear. Budgetary pressures and increasing eligibility criteria are altering the balance of care between residents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Currently, there is no universally accepted terminology for HwC within the sector. Other terms used in the UK include "extra care housing", "assisted living", "very sheltered housing", "independent living", "service-enriched housing", "integrated care", "supported housing", "supported living", "continuing care", "flexi-care", "retirement villages", "retirement communities" and, most recently, "integrated retirement communities" (Howe et al, 2012;ARCO, 2021;Elderly Accommodation Counsel, 2021b, 2022. All these terms are used to describe types of retirement living that provide more services and facilities than traditional sheltered and retirement settings (Elderly Accommodation Counsel, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there is no universally accepted terminology for HwC within the sector. Other terms used in the UK include "extra care housing", "assisted living", "very sheltered housing", "independent living", "service-enriched housing", "integrated care", "supported housing", "supported living", "continuing care", "flexi-care", "retirement villages", "retirement communities" and, most recently, "integrated retirement communities" (Howe et al, 2012;ARCO, 2021;Elderly Accommodation Counsel, 2021b, 2022. All these terms are used to describe types of retirement living that provide more services and facilities than traditional sheltered and retirement settings (Elderly Accommodation Counsel, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…HwC provides independent living, with each resident having their own front door and the full legal rights associated with being a tenant, homeowner or shared owner, and access to communal facilities and 24-h on-site care delivered flexibly according to changing needs (Evans, 2014; Riseborough et al , 2015). There are a multitude of models under this one umbrella with apparently no single mode of delivery, making it difficult to carry out larger-scale studies (Atkinson et al , 2014; Darton, 2022). Huge variations exist in terms of built form, services and facilities provided, management arrangements and pricing structures (Elderly Accommodation Counsel, 2021b).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes older people living with dementia, however, there remains little evidence as to what works best, and for whom, with respect to ECH for people living with dementia (O’Malley and Croucher, 2005; Dutton, 2010; Twyford, 2016). Darton (2022, p. 303) notes that although “research studies have identified the potential benefits and challenges of providing specialist housing […] a number of issues require further research, for example supporting people with dementia”.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of ECH for the general population are now more widely understood (Darton, 2022; Evans and Vallelly, 2007; Holland, 2015), although it should be noted more recent research has suggested financial pressure can result in more task-centred care (Cameron et al , 2020; Darton, 2022). However, there are approximately one-fifth of residents in ECH living with dementia (Barrett, 2020a) where little is known about their experiences of different models of ECH (Dutton, 2010; O’Malley and Croucher, 2005; Twyford, 2016).…”
Section: Introductionmentioning
confidence: 99%